Probability and statistics - Spiegel, Murray R.; Schiller, John J.; Srinivasan, R. Alu. (New York : McGraw-Hill, 2009)
A study-guide to probability and statistics that includes coverage o f course concepts and 897 fully solved problems.
Part I: Probability -- Basic Probability -- Random Variables and Pro bability Distributions -- Mathematical Expectation -- Special Probabili ty Distributions -- Part II: Statistics -- Sampling Theory -- Estimatio n Theory -- Tests of Hypotheses and Significance -- Curve Fitting, Reg ression, and Correlation -- Analysis of Variance -- Nonparametric Tests -- Bayesian Methods.
Includes indexes.
Keywords: Probabilities -- Problems, exercises, etc; Probabilities -- Outlines, syllabi, etc; Mathematical statistics -- Problems, exercises, etc; Mathematical statistics -- Outlines, syllabi, etc